Large‐Pore Functionalized Mesoporous Silica Nanoparticles as Drug Delivery Vector for a Highly Cytotoxic Hybrid Platinum–Acridine Anticancer Agent. Issue 14 (14th February 2017) - Zheng, Ye; Fahrenholtz, Cale D.; Hackett, Christopher L.; Ding, Song; Day, Cynthia S.; Dhall, Rohan; Marrs, Glen S.; Gross, Michael D.; Singh, Ravi; Bierbach, Ulrich
Abstract: Large‐pore mesoporous silica nanoparticles (MSN) were prepared and functionalized to serve as a highly robust and biocompatible delivery platform for platinum–acridine (PA) anticancer agents. The material showed a high loading capacity for the dicationic, hydrophilic hybrid agent [PtCl(en)( N ‐[acridin‐9‐ylaminoethyl]‐ N ‐methylpropionamidine)] dinitrate salt (P1A1 ) and virtually complete retention of payload at neutral pH in a high‐chloride buffer. In acidic media mimicking the pH inside the cell lysosomes, rapid, burst‐like release ofP1A1 from the nanoparticles is observed. Coating of the materials in phospholipid bilayers resulted in nanoparticles with greatly improved colloidal stability. The lipid and carboxylate‐modified nanoparticles containing 40 wt % drug caused S‐phase arrest and inhibited cell proliferation in pancreatic cancer cells at submicromolar concentrations similar to carrier‐freeP1A1 . The most striking feature of nanoparticle‐deliveredP1A1 was that the payload did not escape from the acidified lysosomal vesicles into the cytoplasm, but was shuttled to the nuclear membrane and released into the nucleus. Abstract : Efficient delivery : A highly robust pH‐responsive nanodelivery system was designed for potent DNA‐targeted platinum–acridine hybrid anticancer agents. The biocompatible silica‐based material shows unprecedented drug retention–burst release characteristics and delivers the cytotoxic payload to its final destination in cancer cells, the nucleus.